A Reflective Evaluation Model for Character Education in Arabic Language Learning - Hikmah Maulani; Nalahuddin Saleh; Dadan Mardani; Jenal Bustomi; Muthi Al-Ushali; Aan Hasanah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2025)
This study aimed to develop a Reflective Evaluation Model of Character Education in Arabic language learning within Indonesian higher education using a phenomenological approach. Employing a qualitative phenomenological design, the study explored lecturers’ and students’ lived experiences and reflective practices in integrating character education into Arabic instruction. Data were collected through in-depth interviews, classroom observations, and document analysis and were analysed using Interpretative Phenomenological Analysis to identify core themes. The findings indicated that Arabic language learning was experienced as a meaningful space for character development and perceived as intrinsically linked to moral and spiritual values. Reflective practices emerged across three interrelated dimensions—reflection in action, reflection on action, and reflection for action—which mediated the internalization of character values through curriculum and pedagogy and their manifestation in students’ behaviour. In conclusion, the study proposed a theoretically grounded reflective evaluation model that explains how character education is embedded in Arabic language learning and offers conceptual implications for character-based pedagogy and assessment in higher education.